Synthesis and physicochemical study of polyester polyols of epoxy resin of 2, 4, 6‐tris(4‐hydroxyphenyl)‐1, 3, 5‐triazine and their polyurethanes. Issue 9 (3rd December 2013) - Ghumara, Rizwan Y.; Patel, Jignesh P.; Adroja, Pooja P.; Parsania, Parsotam H.
ABSTRACT Polyester polyols of ricinoleic acid (ETPRA), oleic acid, linoleic acid (ETPLA), and rosin (ETPR) and epoxy resin of 2, 4, 6‐tris(4‐hydroxyphenyl)‐1‐3‐5‐triazine (ETP) and their polyurethanes (PUs) were synthesized and characterized by Fourier transform infrared spectroscopy, NMR, differential scanning calorimetry, and thermogravimetric analysis techniques. The PU films showed the following density order: ETPRPU600 > ETPRAPU600 > ETPLAPU600. ETPLAPU600 showed good tensile strength and volume resistivity values compared to ETPRAPU600 and ETPRPU600. All three PUs showed good electric strength. ETPLAPU600 showed almost double the electric strength of ETPRAPU600 and ETPRPU600. The incorporation of soft‐segment poly(ethylene glycol) 600 into PU chains resulted in the flexibility of the films. The PU films showed a high water absorption tendency in water, acidic, and saline environments, and they degraded in an alkaline environment. The weight gain tendency of the films was due to surface solvolysis and was also probably due to microcrack formation. The polyester polyols and PUs were thermally stable up to about 167–221 and 184–214°C, respectively, and followed multistep degradation reactions with either fractional or integral order (0.43–2.71) degradation kinetics. Thus, the structure of the PUs affected the studied physicochemical properties of the films. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40203.